2024
DOI: 10.1002/zamm.202300647
|View full text |Cite
|
Sign up to set email alerts
|

Numerical computation of joule heating and chemical reaction for the radiated Casson fluid on the slender parabolic surface

T. Salahuddin,
Muhammad Awais

Abstract: This work dealing to solve the numerical results of magnetohydrodynamic flow material (Casson fluid) moving over the slender parabolic surface with temperature dependent viscosity. To make the enhancement in the thermal and solutal fields, we have determined the impact of thermal radiation, viscous dissipation, joule heating, and chemical reaction on the considered flow material. Due to huge applications in coating processes and aerodynamic industries, the suction/Injection is assumed at the surface. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Some key investigations related to the fluidic system performance are described in the refs. [11][12][13]. The authors found very interesting heat transfer results for various sorts of nanofluids and suggested these as better for numerous engineering applications.…”
Section: Introductionmentioning
confidence: 95%
“…Some key investigations related to the fluidic system performance are described in the refs. [11][12][13]. The authors found very interesting heat transfer results for various sorts of nanofluids and suggested these as better for numerous engineering applications.…”
Section: Introductionmentioning
confidence: 95%